Investigation on the damage evolution in the impacted composite material based on active infrared thermography. (October 2016) - Li, Yin; Yang, Zheng-wei; Zhu, Jie-tang; Ming, An-bo; Zhang, Wei; Zhang, Jin-yu
Abstract: A novel method was proposed to investigate the damage evolution of the impacted composite laminate using active infrared thermography in this work. This method was comprised of the following procedures. Firstly, the infrared images, containing the damage information under different fatigue cycles, were obtained through fatigue test and damage detection test. Then, the damage area of the impacted composite laminate being inspected under different fatigue cycles was acquired through such infrared image processing as image enhancement, image segmentation and quantitative identification. Finally, an expression, indicating the relationship between the fatigue cycles and the damage area, was fitted by the least square method. Four specimens were implemented to validate the effectiveness of the proposed method via the proposed procedures. The results indicate that the proposed method can effectively reveal the damage evolution. I.e. the expressions can be accurately fitted and the corresponding accuracy can be as high as 0.98186, 0.95067, 0.9797 and 0.99316 respectively. Highlights: Damage evolution of composite laminate is studied by active infrared thermography. The damage can be quantitatively evaluated by the proposed procedure. An amazing phenomenonoccurs in damage evolution of impacted composite materials. The damage evolution can be fitted by nonlinear fatigue cumulative damage model.